(untitled) (Revista de Artes Marciales Asiáticas, 2025)
Anaerobic metabolism is crucial to Brazilian jiu-jitsu athletes (BJJ), principally during the decisive moments of the match, to perform sweeps, throws, and ground techniques. However, little is known about the association between anthropometric variables with anaerobic performance. Objectives: To describe the peak power (PP) and mean power (MP) obtained in the Wingate test by BJJ athletes, to investigate the correlations between PP and MP and anthropometric variables, and to identify the anthropometric predictors of anaerobic performance. Methods: Twenty male BJJ athletes (aged: 22.9 ± 2.3 yrs, height: 1.75 ± 0.05 m, and body mass: 75.7 ± 10.3 kg) performed a 30 s Wingate test. Anthropometric variables, body mass (BM), fat free mass (FFM), muscle mass (MM), fat mass (FM), and percentage fat mass (%FM) were measured through electric bioimpedance. Results: Absolute mean values for PP and MP were 926 ± 154 and 665 ± 110 W, respectively, whereas relative values to BM were 12.2 ± 1.3 and 8.8 ± 0.9 W.kg-1, respectively. The mean FI value was 30.0 ± 4.7%. A significant and positive correlation was observed between PP and MP with all anthropometric variables (MM, FFM, %FM, FM). FFM was the best predictor of both PP (R2 = 0.69, p = .001) and MP (R2 = 0.67, p = 0.001) in the Wingate test. Conclusions: The results of this study demonstrated that FFM was the main anthropometric variable associated with anaerobic performance in BJJ athletes. Improving FFM may be a key strategy for enhancing anaerobic performance in this population.